Cardiovascular impact of post-traumatic stress disorder: A systematic review and meta-analysis - Bijaya K Padhi (16823745) (2024)
Background Post-traumatic stress disorder (PTSD) is increasingly recognized for its effects beyond mental health, with emerging evidence suggesting a significant association with cardiovascular diseases (CVD). This systematic review and meta-analysis aimed to synthesize available evidence on the association between PTSD and various cardiovascular outcomes. Methods We conducted a comprehensive literature search in databases until March 15, 2024. Studies were included if they were observational in design and assessed the association between PTSD and cardiovascular outcomes. Data were extracted on study characteristics, participant demographics, PTSD assessment, cardiovascular outcomes, and effect estimates. Meta-analyses were performed using random-effects models, and heterogeneity was assessed using the I² statistic. All statistical analyses were conducted using R software version 4.3. Results Twenty studies met the inclusion criteria, encompassing a total of over 335,000 participants. The pooled analyses demonstrated a statistically significant increased risk of any CVD (HR = 1.417, 95 % CI: 1.313-1.522), MI (HR = 1.415, 95 % CI: 1.331-1.500), and stroke (HR = 2.074, 95 % CI: 1.165-2.982) associated with PTSD. Substantial heterogeneity was observed across the studies for stroke and MACE, and evidence of publication bias was noted. Conclusion This meta-analysis confirms a significant association between PTSD and an increased risk of several cardiovascular outcomes, indicating the importance of integrating cardiovascular risk management with psychiatric care for PTSD patients to mitigate the heightened risk of CVDs. Future research should focus on exploring the underlying mechanisms and potential interventions to manage both PTSD and its associated cardiovascular risks effectively. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2024.102632